State Estimation of Power System Embedded with FACTS devices and PMUs - Venkateswaran V, Balaji; Kumar Sharma, Neeraj; Yadav, Deepali (International Journal of Engineering and Technology, 2018)
In recent days, the power system is incorporated with Flexible AC Transmission System (FACTS) devices for compensation of reactive power to maintain the stability of the system. The stability of the system is highly dependent on the state variables which are the outcomes of a state estimator in the power system. To improve the efficiency of a state estimator, high precision measuring devices such as Phasor Measurement Units (PMUs) are installed in the power system. Hence a state estimator embedded with these compensatory devices and PMUs is necessary for estimation of state variables. The present work has been carried out in three steps. Step 1: Considering the cost of PMUs and the availability of the communication network in the particular location, PMUs are optimally placed in the nodes of the system so that all critical measurements are transmuted into redundant ones using differential evolution (DE) algorithm to perform observability analysis. Step 2: A hybrid state estimation is performed by including the mathematical model of FACTS devices and PMUs. Step 3: It is shown that by installing optimal number of PMUs at desired location, multiple bad data detection and identification capability of residual method is considerably improved. Lastly, numerical simulation with standard IEEE 14 bus system, IEEE 118 bus system and a practical 246 bus system of northern region power grid (NRPG) is presented to confirm the effectiveness of the proposed approach in assessing the estimation of the system state variables.